Lower concentration of thalamic N-acetylaspartate in patients with schizophrenia: A Replication Study - Ende, Gabriele; Braus, Dieter F.; Walter, Sigrid; Henn, Fritz A. (The American journal of psychiatry, 2001)
OBJECTIVE: Using proton magnetic resonance spectroscopic imaging, the authors measured thalamic N-acetylaspartate (NAA) concentrations in patients with schizophrenia. METHOD: The study included 15 schizophrenic patients on a stable medication regimen and 15 age-matched healthy comparison subjects. Concentrations of NAA, creatine plus phosphocreatine, and choline-containing compounds in bilateral thalamic regions were determined. RESULTS: Previous findings of lower NAA concentration in the left and right mediodorsal region of the thalamus and significant correlations between left and right thalamic NAA measures in patients with schizophrenia were corroborated. Furthermore, the concentrations of choline-containing compounds were significantly lower in the schizophrenic patients. No group differences in creatine plus phosphocreatine were found. CONCLUSIONS: There is strong evidence for neuronal dysfunction or loss in the mediodorsal region of the thalamus in patients with schizophrenia.